Peningkatan Kerjasama dan Hasil Belajar IPAS Menggunakan Model Student Teams Achievement Division Kelas VSDN 04/II Jaya Setia - Syalsa Dwi Desta; Subhanadri Subhanadri; Puput Wahyu Hidayat (Master of Pedagogy and Elementary School Learning, 2026)
Abstract: This research is motivated by learning in the classroom which is still teacher-centred, resulting in students being less active and reluctant to work together in groups, as well as low science learning outcomes for class V SDN 04/II Jaya Setia. This research aims to evaluate the increase in collaboration and science learning outcomes throught the implementation of the Student Teams Achievement Division model for class V SDN 04/II Jaya Setia. This study is categorized as classroom action research which applies and quantitative approaches with research subjects of 24 grade V students at SDN 04/II Jaya Setia. The research process consists of two cycles, each of which includes planning steps, implementation of observation and reflection, data collection techniques using observation, survey, questionnaire, test, learning outcomes and documentation. This research took place during the even semester of the 2024/2025 academic year at SDN 04/II Jaya Setia. Analysis of research data proves that the use of the STAD model is able to improve cooperation and learning outcomes in grade V science at SDN 04/II Jaya Setia. This evidence can be seen from the results of teacher observations in cycle I ith an average of 73,91% which increased to 89,13% in cycle II. Observations of students also showed a development from 49,16% in cycle I to 81,25% in cycle II. Student cooperation increased from an average of 58,33%. In cycle I it became 83,33% in cycle II meanwhile the student learning outcomes in cycle I showed 16 students completed (66,67%) while in cycle II it rose to 20 students (83,33%). Thut it can be concluded that the STAD model has proven to be effective in increasing collaboration and science learning outcomes for grade V SDN 04/II Jaya Setia.